PARENNIALISM MODEL WITH QUANTUM PHYSICS IN TEACHER SELF TRANSCENDENCE - Nuraeni Asriyanti; Achmad Buchori; Ngurah Ayu Nyoman Murniati (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2025)
The teacher is a moral agent, Maslow’s hierarchy of needs which ends in self-actualization is proven to be unable to bring individuals to find their identity. Problems arise when teachers are oriented towards the love of creatures, material or power. Parennialism with the concept of universal divinity, lowers the perception that the mechanism of the universe including humans can be explained through the nature of matter and energy. A consistent scientific model was found after analyzing the phenomena experienced by the key informant, namely a teacher who proceeded from the initial level to the peak of self-transcendence through the discovery of ‘meaning’. His awareness was instilled through an auto-suggestion pattern, then the key informant was guided to find out the biggest negative energy that moved him. The teacher is likened to the property of a particle insulated by a spin magnitude, and the location of the valence electrons with the greatest energy in the uncertainty region is indicated by the electron configuration. Initially fana al-nafs (0), matter (neutrons) is fissioned until meaning is found as energy, the magnitude of meaning energy (E) depends on how many reactions there are, then and c is the velocity of emission of β particle was constant in terms of the moment of inertia. Like the stability of heavy atomic nuclei after fission can be recovered by releasing β particle emissions, with a ratio of neutron (N) and proton (Z) namely . Surrender leads to the concept of no god (0) but God (1).